Feasibility study on the establishment and operation of a control lumber depot located in a member state of the Caribbean Common Market. Part 2 (FIRA International StevanageGB, 1992)
Recommends that the Forestry Commissions of all the CARICOM lumber producing countries need to be united under one common policy - the National Forestry Action Plan, and that the Commissions should be overseen by a more senior body in the CARICOM Forestry Board. Suggests that as an alternative to the distribution depot outlined in the CARICOM brief, a CARICOM Timber Marketing and Management Organisation should be established.
DC